Olfaction in patients with allergic rhinitis: an indicator of successful MP‐AzeFlu therapy. Issue 3 (26th November 2016) - Klimek, Ludger; Poletti, Sophia C.; Sperl, Annette; Spielhaupter, Magdalena; Bardenhewer, Cornel; Mullol, Joaquim; Hörmann, Karl; Hummel, Thomas
Abstract : Background: The purpose of this study was to investigate the effect of MP‐AzeFlu on olfaction and the interaction between severity of allergic rhinitis and olfactory improvement after therapy. Methods: A prospective, multicenter, observational study was performed on 47 patients with persistent allergic rhinitis. Duration and severity of allergic rhinitis was diagnosed and classified using the modified Allergic Rhinitis and its Impact on Asthma (ARIA) criteria and the proof of allergen sensitization from positive skin‐prick tests, specific immonoglobulin E (IgE) in serum, and nasal provocation response. Patients were treated with MP‐AzeFlu (1 spray/nostril twice daily) over 3 months. Olfactory function was assessed at baseline and at 1 and 3 months of therapy using the "Sniffin' Sticks" test. In addition, a nasal symptom score was recorded on a visual analog scale (VAS) at each given time‐point. Results: MP‐AzeFlu was found to be associated with a significant improvement in TDI score, from 23.7 at baseline to 34.2 at 1 month ( p < 0.001) and 37.1 at 3 months ( p < 0.001) of treatment. Furthermore, a highly significant improvement of symptoms over time ( p < 0.001; VAS at baseline: 84.3; 1 month: 32.4; 3 months: 26.2) could be demonstrated. Most importantly, there was a highly significant interaction between the severity of allergic rhinitis and olfactory function ( p < 0.001) and VAS ( p < 0.001). Conclusion: MP‐AzeFlu is associated with olfactory improvement in persistent allergic rhinitis patients. Further, the modified ARIA severity classification is an indicator of patients' olfactory function. Moreover, assessment of olfaction seems to be a reliable indicator of the clinical success of antiallergic/antiinflammatory therapy.